Construction and Validation of a Cognitive Engagement Scale and Its Relationship with Ball Movement Sequence Performance in Rhythmic Gymnastics - Jasem, Zeena Khaled; Mohammed , Khaleel Setar (مجلة دراسات وبحوث التربية الرياضية, 2024)
The research aims to: build and record a measure of cognitive participation among second-year female students at the College of Physical Education and Sports Sciences, University of Baghdad. The researchers used the descriptive approach in the survey style for the research sample. The sample was selected from female students and divided into: (10) female students for the survey sample, and (80) female students for the construction and codification sample. The data were statistically analyzed by the researchers using SPSS, the T-test for independent and correlated samples, Pearson’s simple correlation coefficient, Cronbach’s alpha, Chi-square, and Spearman-Brown. They were recruited for the samples. The study concluded that constructing a measure of cognitive participation for students in the second stage could be applied through the ease and difficulty of its expressions that are appropriate to the research sample, as well as the grades and levels that were reached, which showed that the sample fell within the rating (good and acceptable), and on the other hand the sample was characterized by participation. Cognitive through the results of the scale and its four axes. In conclusion, cognitive participation plays a positive role in performing the ball movement sequence in rhythmic gymnastics.